The yellow pecan aphid, Monelliopsis pecanis Bissell, in Sicily (Bollettino di zoologia agraria e bachicoltura, 2024)
Outbreaks of tbe yellow pecan aphid, Monelliopsis pecanis Bissell, have beendetected for the first time in Sicily during 1999. This aphid pest is native fromNorth America, where it is widespread from USA to Mexico, and was introducedalso in South Africa and Egypt. Adult viviparous are all alates and large populationsdevelop on lower surface of pecan leaves, witb two seasonal peaks, in latespring and early autumn, respectively. The aphid is holocyclic, overwintering asegg, laid on its host plant twigs. It is responsable of yield-losses by reducing plantenergy, inoculating saliva and growing of sooty mold, all of which negativelyaffect tbe host plant physiology.
Keywords: Monelliopsis pecanis; yellow pecan aphid; Carya illinoensis; pecan